Implementasi Kebijakan Diskresi Pada Pelayanan Kesehatan Badan Penyelenggara Jaminan Kesehatan (BPJS) - Suprapto suprapto; Andi Abdul Malik (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Bureaucratic discretion in regional government as an effort to publish public service effectiveness in a state of urgency, which is a situation that emerges suddenly concerning the public interest that must be resolved quickly, where to resolve the issue, laws and regulations have not yet regulated it. Constraints In bureaucratic discretion in local government as one of the efforts in the effectiveness of public services is the insufficient cost due to excessive demand from the bureaucratic discretion program, policy participants who swell are not in accordance with the established plans, for example, participants who are not categorized as poor but ask to be classified as poor families and administrative services are not smooth because the bureaucratic discretion policy is more a spontaneous program from the local government. The ideal discretion model to overcome the problem of delegation of authority that occurs during diving This is to provide additional competency training in medical action to nurses with the aim that nurses are able to provide limited medical treatment services in accordance with the duties and authorities listed in the Nursing Act. In the development of public administration so many dynamics arise, starting from the role of separate public administration at all with the political world. The next understanding that then emerged was that administration was part of politics. The paradigm that arises is